1987
DOI: 10.1126/science.3120311
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Sequence-Specific DNA-Cleaving Peptide

Abstract: A synthetic 52-residue peptide based on the sequence-specific DNA-binding domain of Hin recombinase (139-190) has been equipped with ethylenediaminetetraacetic acid (EDTA) at the amino terminus. In the presence of Fe(II), this synthetic EDTA-peptide cleaves DNA at Hin recombination sites. The cleavage data reveal that the amino terminus of Hin(139-190) is bound in the minor groove of DNA near the symmetry axis of Hin recombination sites. This work demonstrates the construction of a hybrid peptide combining two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 23 publications
(20 reference statements)
3
103
0
Order By: Relevance
“…This phenotype enables us to study the binding of Hin to hix recombination sites in vivo and to separate binding from subsequent steps in the recombination reaction. These results are consistent with results found in the characterization of the in vitro properties of Hin binding to the hix sites (Sluka et al 1987;A. Glasgow and M. Simon, unpubl.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This phenotype enables us to study the binding of Hin to hix recombination sites in vivo and to separate binding from subsequent steps in the recombination reaction. These results are consistent with results found in the characterization of the in vitro properties of Hin binding to the hix sites (Sluka et al 1987;A. Glasgow and M. Simon, unpubl.…”
Section: Discussionsupporting
confidence: 82%
“…We found three single base pair substitutions among 15 mutations sequenced in hixR. These include an A : T to G : C substitution at position 4; a change in a base shown to be important in minor groove contacts between Hin and hixR in vitro (Sluka et al 1987; A. Glasgow and M. Simon, unpubl.). Among 34 UV-induced hixL mutations, we found four different single base pair substitutions that change base pairs at positions 5 and 6 in both half-sites.…”
Section: Genes and Developmentmentioning
confidence: 99%
“…Each hix site is homologous and the hix half-sites with the highest affinity for Hin have been used to design a fully symmetrical consensus hix site, hixC (Table 1B; Johnson and Simon, 1985;Glasgow et al, 1989a;Hughes et al, 1992). A C-terminal 52-amino-acid polypeptide of Hin recombinase (residues 139-190) has been shown to contain the DNA-binding domain (Sluka et al, 1987). Biochemical and crystallographic data have demonstrated that a helix-turn-helix structure (residues 149 to 180) makes specific contacts in the major groove with nucleotides at positions 9 and 10 of the hix half-site (Glasgow et al, 1989a;Sluka et al, 1990;Hughes et al, 1992;Feng et al, 1994b) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structures of both the holoprotein and a co-crystal with trpEDCBA have been solved (Sluka et al 1987;Otwinowski et ai. 1988).…”
Section: Escherichia Coti Trp Repressormentioning
confidence: 99%